Disentangling effects of policy reform and environmental changes in the norwegian coastal fishery for cod - Diekert, Florian; Schweder, Tore (Land economics, 2017)
We construct a detailed bioeconomic model of the Norwegian coastal cod fishery. This fishery has been open access up to the policy change during the "cod crisis" of 1989/1990. To answer to what extent the subsequent increase in biomass and profits was due to improved management, we isolate the effect of environmental variability. Projecting stock and harvest forward in the counterfactual scenario of no intervention, we show that the policy had a small positive impact on biomass, but a pronounced positive effect on profit. The main drivers of profit gains are increases in productivity and savings in fuel and labor costs.